Combined surgical and medical treatment of a retroperitoneal lymphatic-venous malformation presenting with significant haemorrhage - Mariana Morgado; Sara Lobo; Elizabete Vieira; Luisa Lobo; Miroslava Gonçalves (Elsevier, 2018)
Lymphatic-venous malformations are rare congenital defects resulting from the abnormal communication between lymphatic vessels and systemic circulation, integrating the group of combined vascular malformations, with low-flow. They affect both genders equally and present preferably in the head and neck (>90%), rarely in retroperitoneal location. Clinical diagnosis can be challenging since presentation is highly variable. Surgical resection is the gold standard but, in complex malformations or when facing incomplete surgical resection due to inaccessible location, combined medical and surgical approaches can improve the prognosis. The authors report a case concerning a three-month-old infant with a retroperitoneal lymphatic-venous malformation, with an uncommon life-threatening presentation and a successful combined medical and surgical approach. In the light of this case report, a specific literature review is discussed. Keywords: Vascular malformation, Lymphovenous malformation, Hemolymphangioma, Low-flow vascular malformation, Retroperitoneum, Hemoperitoneum, Propranolol